Pengukuran Aspek Teknologi Pada Industri Kreatif Kerajinan Sangkar Burung Dengan Teknometrik - Novanda, Tigo Nanda; , Etika Muslimah, S.T., M.T; , Much Djunaidi, S.T., M.T (2015)
The industry a cage bird mojosongo an industry main product of the city creative surakarta at once a searching eye of the majority of the the area .But all this time the role of governments in support of the creative industries a cage bird is weak especially in the aspect of technology , some policies taken also did not based with scientific study so it is not the priority guidance that directed based on scientific study .A method of teknometrik is a method that divides technology be a combination of 4 basic component namely technoware , humanware , infoware organware and which are dynamically integrate in the process a transformation that the result of a sum to four of the components were or tcc ( technology contribution coefficient ) used in look at the level the application of aspects of his technology .The purpose of this research he did for measuring from the perspective of the application of technology and the results used to know the contribution of 4 tekn components `